(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In the context of Uzbek literature of the 20th century and the period of independence, the article explains the principles of development of the literary environment of Jizzakh on the example of the works of creators from Jizzakh and reveals the unique ideological and artistic features and common aspects of the literary environment, connecting the artistic world of the creator with local color. intended to learn lip. In the article, in the study of the literary process of the Jizzakh oasis, the principles of the development of the historical, socio-cultural, literary situation of the created environment, in particular, the periodical study of the literary environment in the style of the 20th century and the era of independence, collecting sources related to the life and literary heritage of creators, the created works to analyze from an ideological and artistic point of view, to determine the aesthetic ideal aspect of the literary heritage of creators based on the analysis of artistic works, to illuminate the place of classical literature in the work of the representatives of this literary environment, to observe the issue of nationality and universality, and to reveal their artistic skill and stylistic uniqueness focused on giving. As a result: under the influence of classical literary traditions in the oasis literary environment, the synthesis of religious-mystical and philosophical-social views in poems such as "Bakhshida Navoi", "Dervish Navoi ", "Read verses from Navoi", "Longing Yakhud" process is proven. In the 20th century and during the period of independence, prose works such as "Returnable Waves", "Crying", "Gulzor Village Gulduraklari", "Murder in the Field Yard" created by the artists of the oasis have a local and national color, and the artistic skills of the writers in creating a heroic character and portrait. The formation and development of the literary environment of the Jizzakh oasis in the 20th century and the period of independence was determined by the examples of poetic and prose works of Ibrahim Donish, Turob Maqsud, Abdulla Ahmed, Zulfia Boriyeva, Mehriban Abdurahmanova, Shahlo Ahrorova, Zuhra Mamadaliyeva.